Congenital peritoneal encapsulation - A cause of intestinal strangulation in a child - Marek Wolski; Maria Żerańska; Anna Piotrowska; Karolina Pomorska; Andrzej Kamiński (Elsevier, 2017)
Congenital Peritoneal Encapsulation (CPE) is a very rare condition originating from intestinal malrotation during the 12th week of gestation. Most of the time asymptomatic it can however lead to intestinal obstruction. Sclerotising Encapsulating Peritonitis and Abdominal Cocoon, that are both of inflammatory origin have to be considered in the differential diagnostics. A case of CPE in a 12 years old patient is presented that was a cause of bowel strangulation.